The economics of money and banking - Chandler, Lester Vernon (New York: Harper & Brothers, 1959)
Chandler's new edition is clearly one of the best available texts on money and banking. The central interest of this book is in policy. In addition the book employs theoretical, institutional, historical context within which policymakers operate and by which their policies are shaped. The book employs theoretical, institutional, and historical approaches. It emphasizes an evolutionary view, attempting not only to explain how present-day structures, attitudes, and policies evolved but also suggest some possible directions of future change. The book concentrates on the functioning of the monetary and banking system as a whole and its relationships with the rest of the economy.
rpm 27/04/2018
Loans
Keywords: Money; Banks and banking